FATIGUE STUDY OF A CIRCULAR SAW SHAFT WITH COSMOSWORKS - Staneva, Nelly (Innovation in Woodworking Industry and Engineering design, 2012)
In the last few years systematic fatigue studies are carrying out in Faculty of Forest Industry. Fatigue analysis of a 3D-model of circular saw shaft is carried out by finite elements method (FEA) with CosmosWorks on the base of the fatigue curve (S-N curve) for carbon steel 45. Different fatigue events are studied – with constant amplitude (stress ratio R=-1) and with changeable amplitude. Plots for total life and damage, rainflow 3-D histograms and damage 3-D histograms are obtained.